The process of communication in the Intimate Relationship among athletes conflict avoidance effort with coach to Develope Achievement Motivation - Winda Nur Ramadhani; Dr. Dra. Sri Budi Lestari, SU (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
The condition in which some athletes still choose to establish an intimate relationship is because it is a source of motivation despite the intimate relationship among fellow athletes is a not liked by any coach in any sport. The background of the research is analyzing the matter which potentially diverts the focus of attention when practicing, also possibilities of decreasing the spirit in exercise. The purpose of this research is to describe the communication process in the intimate relationship of fellow athletes as well as avoiding a conflict with the coach to build motivation in order to be a champion. The purpose of the research is done using the Social Penetration Theory, Theory of Attribution, and Theory of personality. This qualitative descriptive research using the method of Phenomenology. The research site is in Semarang, informants were chosen by purposive methods against 3 pairs of national athletes, which seeks to avoid conflict with their coach while making the intimate relationship, primarily with the who considered the intimate relationship as a barrier to an achievement. The results showed that the communication process of fellow athletes through several stages in accordance with the Social Penetration Theory. In the first stage (early stage or orientation) this communication process is done through direct meetings with four informants while the two other informants through social media, where honesty and sharing are still common as exchanging information about each personality, habits, and things related to professions in their sport. In the second phase (approach) the proximity arises because of the high-intensity communication (meeting each day, chatting, brainstorming). The third phase (the familiar relationship or a romantic relationship) this stage is characterized by an increase in the personal activities like exercise together, hanging out together, to even motivate towards each other match in their own way. The final stage (stable exchange) where the informant underlying their relationship with commitment and faith in a relationship to establish bonding and dependency between them. While the efforts from the athletes to avoid a conflict with the coach is using the win-win solution in which the athletes still weaves intimate relationship but still showed their achievements even improving their performance.Coaches need to build good communication scheme with the athletes to make the athletes dare to show their range of thoughts and feelings aiming at the development of individual capabilities and achievements.